Effects of different drying methods on physical properties and anthocyanin and volatile compound contents of black sweet corn (Zea mays L. Saccharata Sturt) - Wang, Pengyue; Chen, Xue; Wei, Xiqi; Xiong, Bingquan; Pan, Xiaomei; Bai, Juhong; Li, Zidan; Xu, Xiangbo (Frontiers in Nutrition, 2025)
BackgroundBlack sweet corn is a new corn variety that offers nutritional advantages; however, high water content makes it difficult to preserve. Drying is a widely employed postharvest processing technique to enhance shelf-life and economic value of agricultural products through moisture reduction.MethodsIn this study, the effects of hot-air drying (HD), vacuum drying (VD), freeze drying (FD), and microwave drying (MD) on corn rehydration, color, texture, and anthocyanin and volatile compound contents were investigated.ResultsIt was observed that the VD products maintained the texture followed by the FD and MD products. The HD products exhibited poor ready-to-eat performance. All the drying methods exhibited significant impacts on the color of dehydrated black sweet corn, the L* and b* values of the fresh corn samples were significantly improved by the FD and MD treatment. The LC–MS/MS analysis of anthocyanin components showed that the FD and MD treatments could effectively mitigate anthocyanin losses during dehydration. A total of 67 volatile aroma components were identified using HS-SPME-GC–MS, and the number of substances (OAV > 1) having a significant effect on the flavor of the corn products were 24 (VD), 27 (FD), 21 (MD), 27 (HD), and 31 (fresh). The orthogonal partial least squares-discriminant analysis revealed linalool, (e)-2-nonenal, eucalyptol, 1-octen-3-ol, and estragole as the discriminatory differential (VIP > 1) aroma components of corn before and after drying. Furthermore, the relative contents of these five components were higher in the FD samples than in the other samples, followed by the MD samples.ConclusionThis study revealed the effects of different drying methods on the black sweet corn quality and laid the foundation for the selection of applicable drying methods to obtain ideal drying quality of black sweet corn.